Investigated Properties of Ceo2 Doped Y257 Superconductors - Meakniti, Suppanyou; Sangchaisee, Sujittra; Thipbanpot, Paphassara; Kruaehong, Thitipong (Journal of Advanced Development in Engineering and Science, 2026)
Polycrystalline Y2Ba5Cu7O15-X (Y257) samples doped with cerium oxide (CeO2) at concentrations of x = 0, 0.05, 0.10, 0.15, and 0.20 were synthesized via the solid-state reaction method at a sintering temperature of 950 °C. X-ray diffraction analysis revealed a mixture of superconducting and non-superconducting phases. The dominant superconducting phase exhibited an orthorhombic crystal structure (space group Pmmm), while secondary phases included Y2BaCuO5 (Pbnm), BaCuO2 (Im-3m), and Ba2Cu3O6 (Pccm). The fraction of the superconducting phase increased with CeO2 content. Rietveld refinement indicated a slight expansion along the c-axis with increasing cerium doping. SEM imaging showed porous microstructures, while EDX mapping confirmed uniform elemental distribution. Electrical resistivity measurements using the four-probe method demonstrated a gradual increase in critical temperature (Tc) from 89.3 K (undoped) to 93.6 K (x = 0.20), consistent with values for Y123-type superconductors. These findings indicate that CeO2 doping enhances the superconducting phase and improves the critical temperature of Y257 compounds.